Pannekoek and Gorter's marxism - Pannekoek, Anton; Gorter, Herman; Smart, D.A. (London : Pluto Press, 1978)
Archief Wilfried De Pauw
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme